A meta-analysis: the clinical value of PD-1 inhibitor or protein tyrosine kinase inhibitors in the treatment of advanced osteosarcoma - Shi, Binhao; Chang, Junli; Sun, Xingyuan; Ma, Xiaoping; Zhao, Peng; Zhou, Chujie; Wang, Yongjun; Yang, Yanping (Frontiers in Oncology, 2023)
Backgrounds PD-1 inhibitors and TKIs have been used to treat advanced osteosarcoma, but there is still a lack of intuitive data for the comparison of their efficacy. We conducted a meta-analysis to evaluate their therapeutic benefits. Methods A systematic methodological search of five primary electronic databases was performed. Studies with a randomized design of any type about PD-1 inhibitors or TKIs for the treatment of advanced osteosarcoma were included. The primary outcomes mainly included CBR, PFS, OS and ORR, The CR, PR, SD and AEs were the secondary outcomes. The survival period (months) of patients was taken as the main analysis data. Random-effects models were used for meta-analysis. Results Eight immunocheckpoint inhibitors in 327 patients from 10 clinical trials were finally evaluated. For OS, TKIs [11.67 months (95% CI, 9.32-14.01)] show more obvious advantages than PD-1 inhibitors [6.37 months (95% CI, 3.96-8.78)]. For PFS, TKIs [4.79 months (95% CI, 3.33-6.24)] are longer than PD-1 inhibitors [1.46 months (95% CI, 1.23-1.69)]. Although there was no fatal event, attention should still be paid, especially during the combined application of PD-1 inhibitors with TKIs since their obvious AEs. Conclusions The findings of this study suggest that patients with advanced osteosarcoma, TKIs may be more beneficial than PD-1 inhibitors. TKIs combined with PD-1 inhibitors has a bright future in the treatment of advanced osteosarcoma, but we should always pay attention to the strong side effects.